A phase 1 double‐blind, placebo‐controlled study of zuranolone (SAGE‐217) in a phase advance model of insomnia in healthy adults. (5th August 2021) - Bullock, Amy; Gunduz‐Bruce, Handan; Zammit, Gary K.; Qin, Min; Li, Haihong; Sankoh, Abdul J.; Silber, Christopher; Kanes, Stephen J.; Jonas, Jeffrey; Doherty, James
Abstract: Objective: To evaluate single zuranolone (SAGE‐217) 30 or 45 mg doses in a 5‐h phase advance insomnia model. Methods: In this double‐blind, three‐way crossover study, healthy adults received placebo ( n  = 41), zuranolone 30 mg ( n  = 44), and zuranolone 45 mg ( n  = 42) across three treatment periods. Sleep was assessed by polysomnography and a postsleep questionnaire. Next‐day residual effects and safety/tolerability were evaluated. Results: Compared with placebo, zuranolone resulted in significant improvements in median sleep efficiency (30 mg, 84.6%; 45 mg, 87.6%; placebo, 72.9%; p  < 0.001 for both doses), wake after sleep onset (WASO; 30 mg, 55.0 min; 45 mg, 42.5 min; placebo, 113.0 min; p  < 0.001 for both doses), duration of awakenings (30 mg, 4.2 min, p  < 0.001; 45 mg, 3.7 min, p  = 0.001; placebo, 7.4 min), and total sleep time (TST; 30 mg, 406.3 min; 45 mg, 420.3 min; placebo, 350.0 min; p  < 0.001 for both doses). Subjective endpoints (WASO, TST, sleep latency, sleep quality) also improved relative to placebo. Zuranolone was generally well tolerated, and the most common adverse events (≥2 participants, any period) were headache and fatigue. Conclusion: Zuranolone improved sleep measures versus placebo in a phase advance model of insomnia in healthy adults, supporting future studies in patients with insomnia disorder.